Research on Laser Precision Measurement of Helical Angle of Helical Cylindrical Gear - Zi Hao; Song Aiping; Chu Yuegang; Zhou Ye; Yu Chenwei (Jixie chuandong)
A method and device for measuring helical angle of non-contact helical cylindrical gear based on laser displacement sensor is presented. According to the least square method， the collected points on the measured helical gear end section are fitted into a smooth curve （tooth profile）， and the intersection points between the curve and the indexing circle are obtained. Several intersection points of the tooth profile and the indexing circle on different cross sections of the same gear are measured in turn， and then the slope of the straight line is calculated by the coordinate method. The helical angle of helical gear is obtained. The gear measurement method based on laser displacement sensor can effectively improve the accuracy and efficiency of helical gear helical angle measurement， and is also applicable to the accurate measurement of helical gear errors.